Nicotine stomatitis in smokers: a case report - Doni MS. Prabowo; Haris B. Widodo (Journal of Dentomaxillofacial Science, 2018)
Objective: The aim of this study is to describe and analyse nicotine stomatitis in smokers. Of the world population that consumes tobacco, Asia and Australia make up 57% of tobacco consumers. Tobacco can be consumed by various ways such as smoked tobacco, commonly known as cigarettes, or smokeless tobacco. Cigarettes are known to cause nicotine stomatitis in the oral cavity.Methods: A 28-year-old man patient came with complaints of white spots on his hard palate. The patient has a medical history of asthma as a child and has been taking salbutamol. The patient has been smoking 3 packs of cigarettes a day since being 16 years old.Results: Nicotine stomatitis that occurs on the hard palate appears as circular reddish shapes on the orifice of minor salivary glands. These lesions are formed from physically irritation caused by smoking. The lesions were benign and reversible.Conclusion: Thought appropriate examination and treatment, these lesions were healed.